The impact of joint management of water resources of the Tigris and Euphrates basins on the security and stability of Iraq - SHARQI, Assist. prof. Dr. NAHRAIN JAWAD (The college of law and political science journal, 2023)
The two main sources of Iraqi water are the Tigris and Euphrates rivers, which supply (98%) of the country's surface water. Both rivers originate in Turkey, the Euphrates flows through Syria, and some other tributaries flow through Iran. Until the 1970s, Iraq was considered a country rich in water, but since Turkey began building dams on the two rivers, it has greatly reduced Iraq's water resources. The Turkish government initiated the Southeast Anatolia Project, building 22 dams and 19 hydropower stations for the developing provinces in the southeast, and was reluctant to negotiate a water deal with Iraq and Syria. Turkey has the potential to cut off the downstream water flow in the short term, while reducing Iraq's overall water supply. For example, in the 1990s, Turkey raised the water level of the Ataturk Dam without the knowledge of Syria and Iraq. Iran's water sector policies have also reduced Iraq's water supply. As the tributaries that originate from Iran provide (40%) of the water of the Shatt al-Arab (Al-Wand River) in Iraq, and the construction of the dam had a devastating effect on the flow of water to the eastern governorates of Iraq. With the construction of 600 dams in Iran and more planning, the waters of rivers such as Karun and Karkheh were diverted to stay in Iran and no longer flow into Iraq. These deviations in the path not only reduced the flow of water into Iraq, but also increased the salinity of the water. In Basra Governorate alone, 118 thousand people were hospitalized in the summer of 2018, due to health problems related to water quality. Looking to the future, the Tigris and Euphrates rivers inside Iraq are expected to dry up by 2040 due to the water policies of its neighbors, and it seems that there is no solution for Iraq other than resorting to negotiations with upstream countries and agreeing on an integrated management of the waters of the two basins (Tigris and Euphrates) for the sake of water sustainability. and maintaining the security and stability of the country.